2020
DOI: 10.1109/tro.2019.2937471
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Collaborative Robotics Through Automated Formal Verification

Abstract: A crucial aspect of physical human-robot collaboration (HRC) is to maintain a safe common workspace for human operator. However, close proximity between human-robot and unpredictability of human behavior raises serious challenges in terms of safety. This article proposes a risk analysis methodology for collaborative robotic applications, which is compatible with well-known standards in the area and relies on formal verification techniques to automate the traditional risk analysis methods. In particular, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 57 publications
0
44
0
Order By: Relevance
“…Vicentini et al [VARM20] proposed a methodology to assess the physical safety of Human-Robot Collaboration (HRC) via a rich formal model of collaborative systems. The methodology features a model of both normative and erroneous human behavior [AMRV17,AMRV19] in order to detect the hazardous situations caused by human error, which are typically overlooked during the assessment.…”
Section: Supporting the Design Of Robotic Applicationsmentioning
confidence: 99%
“…Vicentini et al [VARM20] proposed a methodology to assess the physical safety of Human-Robot Collaboration (HRC) via a rich formal model of collaborative systems. The methodology features a model of both normative and erroneous human behavior [AMRV17,AMRV19] in order to detect the hazardous situations caused by human error, which are typically overlooked during the assessment.…”
Section: Supporting the Design Of Robotic Applicationsmentioning
confidence: 99%
“…Few researchers and their teams [3,[16][17][18][19][20][21] discussed different industrial environments, the safety approaches that should be followed, and some real-life case studies. it was showed that lead designers must develop and evaluate safe, human-centered, ergonomics, and efficient collaborative assembly workstations, where the operator's feedback was provided in regards to occupational health and safety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other works implement formal languages to capture collaboration: for example, Webster et al [11] develop Brahms models of a robotic personal assistant and then perform modelchecking with the tool SPIN. Vicentini et al [12] use LTL formulae to model collaborative tasks and develop an innovative risk assessment technique. Some works exploit learning techniques to develop their model.…”
Section: Related Workmentioning
confidence: 99%